Current Imbalance in Parallel Battery Strings Measured Using a Hall‐Effect Sensor Array. Issue 4 (7th April 2021) - Luca, Robert; Whiteley, Michael; Neville, Toby; Tranter, Tom; Weaving, Julia; Marco, James; Shearing, Paul R.; Brett, Dan J. L.
Abstract : Current heterogeneities in parallel battery strings may result in accelerated and imbalanced degradation of cells within vehicle battery packs. This paper presents a measurement technique using micro‐Hall effect sensors, small enough to be integrated into module casings, for an on‐board measurement and diagnostic solution for automotive battery packs. This is demonstrated on an 8p1s 18650 module. More details can be found in article number 2001014, Dan J. L. Brett and co‐workers.